THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE MOTIVATION AND PROMOTION AGRIBUSINESS DEVELOPMENT CENTER Germination PLANT FOOD (BP2 APTP) DEPARTMENT OF AGRICULTURE SPECIAL PROVINCE OF YOGYAKARTA - Sri Ispandiyah, Roro; Lastari, S.E., MM, Siwi (Management, 2010)
Institute for Development and Promotion of Agribusiness Food Crop Seed (BP2APTP) Department of Agricultural Special Region of Yogyakarta is the Office engaged in breeding of cereals. At the Center of Agribusiness Development and Promotion of Seed Plant Food (BP2APTP) Department of Agriculture Province of Yogyakarta Special Region employees need to be guided, directed his work is motivated to work effectively and efficiently by the managers who are able to direct, guide and motivate them to do jobs that lead to goals been established if the leadership of Hall of Seed Development and Promotion of Agribusiness Food Park (BP2APTP) Department of Agriculture Province of Yogyakarta Special Region is able to apply effective leadership style to suit the situation faced by the behavior of employees in performing their duties will run optimally they get motivation from the leadership of a good job . From the results of research conducted by the authors it was found that leadership style delegatif is a dominant leadership style in UPTD BP2APTP and there is a weak relationship between leadership style and employee motivation. Keywords: Leadership, Employee.